Analisa dan Perancangan 3D Candi Cetho Menggunakan Metode Polygonal Modeling - Dimas Setiawan; M Suyanto; Hanif Al Fatta (Politeknik Sawunggalih Aji, 2017)
The 3D modeling with scanning and Photogrametry technique become new trendsetter for historical object reconstruction process, however there are many researcher who not use this 3D’s digital modeling tehnique. Polygonal Modeling is digital modeling technique which suitable for make 3D’s model from non organic object like a building. Cetho Temple is the historical building who use 2D picture as the documentations result, so produce the 3D model for Cetho temple can be use as new alternative for introduce the object for common peoples. The purposes of 3D’s reconstruction is make 3D’s product whose similiar with the original object. Modeling use Polygonal Modeling technique with files textures is better than procedural textures technique who produce 3D models for temple cetho on 87,35% from common peoples and 77,67% from expert medias. Keywords— Digital Modeling, Polygonal Modeling, Cetho Temple, Texturing